Relations, money, and financial skills to fight an attrition war: The Strozzi brothers, bankers and commanders - Michele Maria Rabà (The Journal of European Economic History (JEEH), 2022)
The essay examines the contribution provided by Piero, Roberto and Leone Strozzi - sons of the wealthy Florentine banker Filippo Strozzi - to the French war effort in the last two decades of the Ital- ian Wars. A contribution based on their military and diplomatic skills and on the availability of money, but also on their banking know- how and on consolidated relationships with a widespread network of financiers. These tools were essential in a war of attrition - such as the one waged by the Valois against the Habsburgs for the hege- mony in Europe and in the Mediterranean -, because they allowed the three anti-Medici Florentine exiles to quickly transfer financial resources to the Italian fronts, overcoming the physical distance that separated the king of France's armies in the Peninsula and his fleets in the Mediterranean.
Keywords: 330; Military expenditure; War; Italian; Florence; Italy; France; Militärausgaben; Krieg; Italienisch; Florenz; Italien; Frankreich